Assessing Educators’ Readiness for Innovative Professional and Pedagogical Activities - G. R. Khusainova; S. G. Karstina; M. F. Galikhanov (Высшее образование в России)
The ongoing transformations in the modern world have a significant impact on the sustainable development of national economies, unify the requirements for human capital, and its educational level. Taking into account current trends, governments are taking significant measures to ensure and maintain the link between education, the economy and socio-economic development. These measures also change approaches to engineering training. At the same time, training, retraining, continuing training of educators are of great importance. Educators at present should follow trends of a dynamically changing reality. Thus, the purpose of this work is to assess the educators’ readiness for innovative professional and pedagogical activities (IPPA) in the process of their training on the module “Problembased, practice-oriented, project-based learning”, which is part of the continuing retraining program for engineering teachers iPET-3, developed within the framework of the international project ENTER (“EngineeriNg educaTors pEdagogical tRaining”), co-funded by the Erasmus + program of the European Union. The article proposes a model for the development of educators’ readiness for IPPA within the framework of professional retraining programs, a methodology for assessing the component composition of IPPA, and a three-level characteristic model of the component composition of IPPA. The use of the developed model during continuing retraining programs increases the level of teachers’ creative abilities, the amount of acquired material and their pedagogical skills.